Determinants of Purchase Intention Toward MS Glow: The Moderating Role of Price Discounts - Amelia Juniasi; Andika Nuraga Budiman (SAN Scientific, 2026)
This study aims to determine the effects of brand image, product knowledge, and celebrity endorsement on purchase interest in MS Glow products, with price discount as a moderator. Data was collected using a questionnaire. Data analysis using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that brand image, product knowledge, and celebrity endorsement can serve as a model that influences purchase interest, with price discounts as a moderate variable. Brand image and product knowledge positively affect purchase interest. Celebrity endorsement positively affects purchase interest. Price discounts can moderate, but not weaken, the influence of brand image and product knowledge relative to the original sample value. Price discounts can moderate and strengthen the influence of celebrity endorsement on the original sample value. The managerial implications of this study highlight the importance of building a strong brand image, enhancing consumer product knowledge, and strategically utilizing celebrity endorsements to increase purchase interest. Businesses should invest in consistent brand positioning and reputation management to create a positive perception among consumers.